Pemanfaatan Gulma Eceng Gondok sebagai Penjernih Air - Sutandi, Maria Christine; Genkensiana, Alexander; Mayaut, Cindy Claudia Ivany (Jurnal Teknik Sipil, 2021)
Indonesia is a developing country with a tropical climate with erratic rainfall. Sometimes it rains continuously and there are times when there is no rain at all over a long period of time. When experiencing long rainfall, there is often flooding and of course this flood water is very dirty and generally can not be used for MCK, and so on. The purpose of this research is to make the people at the flood site get clean water. This study uses a method of trial and error by conducting experiments in the laboratory, using models. In this water purification study we use water plants that are water hyacinth where the plant has advantages at the roots, such as maintaining balance when floating and can absorb pollutants (metals) in the water as food and produce the necessary oxygen in the aeration process so that coagulants occur. With this research can be concluded that people affected by floods and isolated can still do their daily activities using clean water and it is expected that this model can be followed up with prototypes